Stylistic heritage and tendencies in contemporary Croatian cinema - Krunoslav Lučić (Images)
This paper focuses on the diverse stylistic heritage and various tendencies in Croatian cinema of the 1990s and 2000s. Since many film scholars accentuate the discontinuity between contemporary Croatian cinema and that from the Yugoslav period, the paper points to continuities in the stylistic trends of both periods. The paper also analyzes two major stylistic configurations ‒ classical and modernist ‒ focusing on different variants of both aesthetic orientations. Variants of cinematic classicism (reduced and excessive classical style) are exemplified by the films of Krešo Golik and Fadil Hadžić, and by the films of Dalibor Matanić and Zrinko Ogresta from the contemporary period. On the other hand, variants of cinematic modernism (realist and psychological) are exemplified by thefilms of Vatroslav Mimica and Ante Peterlić from the 1960s, and in the contemporary period by thefilms of Zrinko Ogresta and Lukas Nola.